Estimates of genetic parameters and genetic trends for milk production traits in Murciano-Granadina goats - J. Ehsaninia; M.B. Zandi; M. Taned; A. Bagheripour (Animal)
Dairy goat production plays a vital role in meeting nutritional needs and supporting rural livelihoods. This study estimated variance components and genetic parameters for daily milk yield (DMY), daily milk fat yield (DMFY), and daily milk protein yield (DMPY) in Murciano-Granadina goats. The study used data collected from 2015 to 2021 in Ghaleh-Ganj dairy goat farm in Kerman province, Iran. R software was used to evaluate environmental effects, examine genetic and phenotypic trends, and determine genetic-phenotypic correlations. The best model was determined based on Akaike’s Information Criterion. (Co)variance components and heritability were estimated using the AIREMLF90 software. For DMY, DMFY, and DMPY, the estimated heritability was 0.21 ± 0.02, 0.13 ± 0.01, and 0.17 ± 0.02, respectively. The repeatability estimates were moderate, ranging from 0.40 for DMPY to 0.46 for DMY. The contribution of animal permanent environmental effect to the total phenotypic variance was estimated as 21, 48, and 17% for DMY, DMFY, and DMPY, respectively. The estimates of genetic correlations between DMY-DMFY, DMY-DMPY, and DMFY-DMPY were 0.62 ± 0.0140, 0.67 ± 0.010, and 0.85 ± 0.009, respectively. Estimates of phenotypic correlations among traits ranged from −0.12 ± 0.006 for DMY-DMFY and DMY-DMPY to 0.35 ± 0.005 for DMFY-DMPY. This investigation revealed moderate heritability and positive and moderate genetic correlations among the observed dairy traits. These results can be used to establish a breeding plan to improve the production level of Murciano-Granadina goats.